Analysis of Critical Discourse on Gender Equality on Instagram Content @Konde.co - Sutriyanti; Lintang Cahya Dewinta Afdellyn; Qismullah Nur Sitepu; Yunita Sari (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the representation of gender equality in digital media by analyzing Instagram content published by the alternative media account @konde.co. The research addresses the persistent issue of gender inequality in domestic and social relations, particularly how women are positioned and narrated within digital discourse. The objective of this study is to explore how women are represented as subjects, objects, and readers in gender-related content and how such representations shape public understanding of gender justice. Employing a qualitative research design, this study uses Critical Discourse Analysis based on Sara Mills' framework, focusing on subject–object positioning and reader positioning within selected Instagram posts. Data were collected through documentation of visual and textual content, observation, and supporting interviews with followers of the account. The findings reveal that women are predominantly represented as subjects experiencing structural injustice, emotional exploitation, and double workload within marriage, while patriarchal norms and male immaturity are positioned as objects of critique. Furthermore, the content strategically positions readers to empathize with women's experiences and critically reflect on unequal gender relations. This study demonstrates that Instagram functions as a counter-discursive space that promotes gender awareness and social justice, contributing to the development of gender-sensitive communication practices in the context of Islamic communication and digital da'wah.